EKSPRESI BAHASA EVALUATIF PADA ARTIKEL ILMIAH BERBAHASA INDONESIA - Fadly, Ahmad; Yuwono, Untung; Suganda, Sonya Puspasari (UI Scholars Hub, 2024)
Authors of scientific articles are faced with two opposing demands: objectivity and critical evaluation when expressing reality and truth. To date, no evaluative language mapping has been performed on Indonesian scientific articles which can accurately describe an article’s degree of objectivity so that it can be used as a tool for objectivizing and negotiating truth. Using the appraisal framework, this research aims to identify and examine these two opposing orientations as they appear in Indonesian scientific articles. The qualitative approach was applied to perform in-depth analysis of interpersonal functions in scientific articles. Data in the form of Indonesian scientific articles were obtained from top ten highest impact factor journals which are accredited and indexed by the Science and Technology Index (SINTA), representing ten different scientific disciplines. Results show that the authors could not completely avoid subjectivity. However, objectivity was clearly sought through five strategies: passivation, verbalization, prioritization of verbs before explicit expressions of affect, nominalization, and prioritization of nouns before explicit expressions of affect. Using the appraisal framework, the modality theory in Indonesian (Alwi 1992), and the lexical semantic theory (Cruse 1986) as bases for data analysis, this research offers a taxonomic evaluative language map of Indonesian scientific articles. This research used the appraisal framework (Martin and White, 2005), especially the attitude and graduation system, to define boundaries while combining objective and evaluative-critical language in three parameters: (1) distance between the personal evaluation source and the evaluative item; (2) the prominence of agentivity and a person’s involvement in the actualization of events; and (3) the root meaning of evaluative lexemes.